2018
DOI: 10.1080/15592294.2016.1264561
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for a nomenclature system for reporting methylation aberrations in imprinted domains

Abstract: The analysis of DNA methylation has become routine in the pipeline for diagnosis of imprinting disorders, with many publications reporting aberrant methylation associated with imprinted differentially methylated regions (DMRs). However, comparisons between these studies are routinely hampered by the lack of consistency in reporting sites of methylation evaluated. To avoid confusion surrounding nomenclature, special care is needed to communicate results accurately, especially between scientists and other health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 14 publications
4
64
0
Order By: Relevance
“…Gene expression is controlled by the methylation status of the two imprinting centres: H19 / IGF2 :IG DMR (also called ICR1 (Imprinting Control Region 1)) for the telomeric domain and KCNQ1OT1 :TSS DMR (also called ICR2) for the centromeric domain (figure 1). 6 In addition to the imprinting centres, enhancers located in both domains control the expression of the genes located in the region. Within the telomeric domain, common enhancers shared by IGF2 and H19 are located 5’ of H19 7.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gene expression is controlled by the methylation status of the two imprinting centres: H19 / IGF2 :IG DMR (also called ICR1 (Imprinting Control Region 1)) for the telomeric domain and KCNQ1OT1 :TSS DMR (also called ICR2) for the centromeric domain (figure 1). 6 In addition to the imprinting centres, enhancers located in both domains control the expression of the genes located in the region. Within the telomeric domain, common enhancers shared by IGF2 and H19 are located 5’ of H19 7.…”
Section: Introductionmentioning
confidence: 99%
“…ICR1 regulates the expression of the non-coding RNA H19 and the IGF2 gene. ICR1 is methylated only on the paternal allele and unmethylated on the maternal allele 6. On the maternal allele, the ubiquitous Zinc-finger DNA-binding protein CTCF can bind to the unmethylated ICR, acting as an insulator and blocking the interaction of downstream enhancers with the IGF2 promoter, leading to transcriptional silencing of IGF2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…155 ). GNAS shows differential methylation at four distinct DMRs: one paternally methylated-DMR (GNAS-NESP:TSS-DMR) and three maternally methylated-DMRs (GNAS-AS1:TSS-DMR, GNAS-XL:Ex1-DMR and GNAS A/B:TSS-DMR, according to the current nomenclature 156 ). Loss of methylation at GNAS A/B:TSS-DMR is detected in all patients with PHP1B 45,47,[86][87][88]101,143,[151][152][153][154] .…”
Section: Molecular Diagnosismentioning
confidence: 99%
“…However, the specific aspect that makes imprinted DMRs unique is not their germline status, but their ability to maintain parent-of-origin allelic methylation during pre-implantation reprogramming (Smallwood et al 2011, Smith et al 2014. To date, there are 38 known germline-derived imprinted DMRs in humans, the majority originating in the oocyte, that retain life-long allelic methylation in adult tissues (Monk et al 2016). It has been shown that imprinted DMRs are selectively protected from the demethylation that occurs in the zygote immediately after fertilization.…”
Section: Genomic Imprintingmentioning
confidence: 99%